Simultaneous removal of arsenic and mercury from natural-gas-co-produced water from the Gulf of Thailand using synergistic extractant via HFSLM - Lothongkum, Anchaleeporn Waritswat; Suren, Sira; Chaturabul, Srestha; Thamphiphit, Nopphawat; Pancharoen, Ura (My University, 2011)
The simultaneous separation of arsenic and mercury ions from natural-gas-co-produced water was well achieved by a synergistic extractant through a hollow fiber supported liquid membrane (HFSLM). Aliquat 336, Bromo-PADAP, Cyanex 923 and Cyanex 471 dissolved in toluene were used as the organic extractants or carriers. The transport system was studied on several variables: types of the extractants, concentration of the synergistic extractant, concentration of H2SO4 (a co-extractant) in feed solution, types of stripping solutions (NaOH, DI water, HNO3, H2SO4 and thiourea), and the number of separation cycles. The results indicated the superior performance of mercury removal to arsenic by every single extractant in this study. The synergistic effect on arsenic removal was observed by adding Cyanex 471 in Aliquat 336 resulting in the synergistic coefficient of 2.8. The regulate mercury discharge to the environment not higher than 5ppb was attained within 1-cycle separation by using the mixture of 0.22M Aliquat 336 and 0.06M Cyanex 471 as the synergistic extractant and 0.1M thiourea as the stripping solution with 0.2M H2SO4 in feed solution. By 3-cycle separation, 94% arsenic extraction, which was below the legislation limit of 250ppb, was obtained. © 2010 Elsevier B.V.
Keywords: Arsenic; Co-produced water; HFSLM; Mercury; Synergistic